Use of Social Media in Agricultural Outreach Activities: A Study at CCS Haryana Agricultural University, Hisar - Partap, Bhanu; Partap, Manju (Journal of Agricultural Extension Management, 2021)
Social media plays a crucial role in this digital era in every human endeavor. The present study aims to evaluate the use of social media and its impact in agricultural outreach activities at Chaudhary Charan Singh Haryana Agricultural University, Hisar. The study found that more than ninety percent of the extension specialists were aware of the social media applications and their use in sharing agricultural information and outreach activities. Further, it was also found that WhatsApp was the most preferred medium of communication among the extension specialists. Social media was used by 36% of the respondents for sharing agricultural information with the farmers' community. It was also suggested that proper awareness and training programs be organized frequently for extension specialists and the farmers' community.